Analysis for non-radiative recombination and resistance loss in chalcopyrite and kesterite solar cells. (15th January 2021) - Yamaguchi, Masafumi; Tampo, Hitoshi; Shibata, Hajime; Lee, Kan-Hua; Araki, Kenji; Kojima, Nobuaki; Ohshita, Yoshio
Abstract: The efficiency potential of chalcopyrite and kesterite solar cells including CIGSe (CuInGaSe2 ), CIGS (CuInGaS2 ), CZTS (Cu2 ZnSnS4 ) and CZTSSe [Cu2 ZnSn(S, Se )4 ] solar cells is discussed based on external radiative efficiency (ERE), open-circuit voltage loss, fill factor loss, non-radiative recombination and resistance loss. CIGSe cells achieve efficiency potential of 26.8% and 27.5% by improving the ERE from around 1% to 10% and 20%, respectively. CIGS and CZTS(Se) cells achieve the efficiency potential of 25% and 22%, respectively, by improvement in ERE from around 1 × 10 −4 % to 3%–5%. The effects of non-radiative recombination and resistance loss upon the properties of wide-bandgap CIGSe, CIGS and CZTS(Se) cells are discussed. In the case of wide-bandgap CIGSe cells, lattice mismatching between the buffer layer and CIGSe active layer and deep-level defects are thought to originate from non-radiative recombination loss. CIGS and CZTS(Se) cells are shown to have lower ERE and higher resistance loss compared to that of CIGSe cells.